2006
DOI: 10.3138/jcfs.37.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Social Values and Self-Disclosure: A Comparison of Chinese Native, Chinese Resident (in U.S.) and North American Spouses

Abstract: Guided by the individualism-collectivism model, the present study examined the relationship between cultural values and marital processes among Chinese native, Chinese residents in America, and North American spouses. Respondents completed a questionnaire which assessed individualism, collectivism and self-disclosure. The results were mixed in their support of the model. As expected, we found that (a) Chinese resident wives were more individualistic than Chinese native wives, (b) Chinese resident husbands were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…India and Puerto Rico were selected because they represent collectivistic cultures and the United States is generally considered to be individualistic. Since Triandis' (1972) monumental contribution to understanding subjective culture and Hofstede's (1980) Culture's Consequences, the constructs of individualism and collectivism have been central to intercultural studies (e.g., Fitzpatrick et al, 2006). In general, collectivistic societies emphasize group cohesiveness, emotional interdependence, obligation, and group solidarity.…”
Section: Individualism and Collectivismmentioning
confidence: 99%
“…India and Puerto Rico were selected because they represent collectivistic cultures and the United States is generally considered to be individualistic. Since Triandis' (1972) monumental contribution to understanding subjective culture and Hofstede's (1980) Culture's Consequences, the constructs of individualism and collectivism have been central to intercultural studies (e.g., Fitzpatrick et al, 2006). In general, collectivistic societies emphasize group cohesiveness, emotional interdependence, obligation, and group solidarity.…”
Section: Individualism and Collectivismmentioning
confidence: 99%
“…Specifically, greater social constraints were only associated with greater symptoms among highly acculturated women. Disclosure is often more highly valued in American than Chinese culture (Fitzpatrick et al, 2006); thus, greater social constraints on disclosure were only associated with greater symptoms among women valuing or expecting disclosure. Relatedly, studies of patients with prostate and colorectal cancer found that socially constraining behaviors were more harmful to mental health for those reporting a greater need for emotional expression (Agustsdottir et al, 2010; Dagan et al, 2014).…”
mentioning
confidence: 99%
“…Quek and Knudson-Martin (2006) also reported that there was significant self-disclosure about important topics among Singaporean spouses. Similarly, past research has revealed linkages between self-disclosure and marital satisfaction for Chinese spouses (Fitzpatrick, Liang et. al, 2006).…”
Section: Conceptual Frameworkmentioning
confidence: 77%
“…Although the specific ways in which spouses communicate might vary across cultures, cross-national studies have revealed that of revelation of information (self-disclosure) or efforts to address problems (conflict tactics) are quite common (Bell & Bell, 2000). For example, past research has shown that self-disclosure and conflict affected marital satisfaction among Chinese and American spouses (Fitzpatrick, Feng, et al, 2006). Given that prior research has demonstrated relevance to marital satisfaction, it seemed worthwhile to examine the role of such proximal factors among Singaporean husbands and wives.…”
Section: Conceptual Frameworkmentioning
confidence: 99%